A linguopragmatic interpretation of the phenomenon of politeness - Ganieva, Dildora Azizovna; Khakimova, Zumradkhon Kudratali qizi (The Lingua Spectrum, 2026)
This article examines the category of politeness beyond the traditional frameworks of ethics and moral norms, treating it as a complex linguopragmatic system that serves to maintain social equilibrium between the speaker and the listener during communication. In the era of globalization, the relevance of this research is determined by the need to study politeness strategies through a synthesis of linguistic, cultural, and cognitive contexts. The paper analyzes fundamental theories such as J. Austin and J. Searle’s Speech Act Theory, P. Grice’s Cooperative Principle, and the “face” concept established by E. Goffman, P. Brown, and S. Levinson. Specifically, the study explores the differences between Western and Eastern discourses, focusing on how linguistic features reflect needs for personal autonomy and collective reputation (positive and negative face). This research holds both theoretical and practical significance for specialists in linguistics, pragmatics, cognitive linguistics, and cultural studies, as well as for researchers involved in discourse analysis.